Study of Factors Making Space-Contaminated Optical System Unusable. (6th September 2012) - Wu, Dakun; Zhou, Yanping; Sun, Fangkui
Abstract : Molecular and particulate contamination of space optical surfaces can be extremely detrimental to optical system performance. In order to determine whether optical system is unusable, we must do a lot of tests. For reducing experimental effort, computational criterion for unusable space optical system is put forward, which is based on experimentation and calculation by 2D-FDTD (finite-difference time domain). And then factors making optical system unusable are studied when distribution of light intensity is consistent with the criterion. Results show that small particulate is more detrimental to optical system than big one for particle with high permittivity is. The distribution of particles making optical system unusable is also obtained.